2014
DOI: 10.1371/journal.pone.0087440
|View full text |Cite
|
Sign up to set email alerts
|

p53 Regulation by TRP2 Is Not Pervasive in Melanoma

Abstract: p53 is a central tumor suppressor protein and its inhibition is believed to be a prerequisite for cancer development. In approximately 50% of all malignancies this is achieved by inactivating mutations in the p53 gene. However, in several cancer entities, including melanoma, p53 mutations are rare. It has been recently proposed that tyrosinase related protein 2 (TRP2), a protein involved in melanin synthesis, may act as suppressor of the p53 pathway in melanoma. To scrutinize this notion we analyzed p53 and TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…These results were inconsistent with the report of Sendoel et al (2010), which suggested reduced p53 expression when DCT was increased in WM266-4 melanoma cells. Our results are consistent with the recent paper by Houben et al (2014), who demonstrated that varying endogenous DCT expression levels in melanoma cells had no effect on p53 protein levels, in that 33% of negative or low DCT-expressing cells had low or negative p53, as did 37% of strong DCT-expressing cells. Moreover, neither efficient DCT knockdown in DCT-positive melanoma cells increased p53 levels, nor did overexpression of DCT in a DCT negative melanoma cell line repress p53 expression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results were inconsistent with the report of Sendoel et al (2010), which suggested reduced p53 expression when DCT was increased in WM266-4 melanoma cells. Our results are consistent with the recent paper by Houben et al (2014), who demonstrated that varying endogenous DCT expression levels in melanoma cells had no effect on p53 protein levels, in that 33% of negative or low DCT-expressing cells had low or negative p53, as did 37% of strong DCT-expressing cells. Moreover, neither efficient DCT knockdown in DCT-positive melanoma cells increased p53 levels, nor did overexpression of DCT in a DCT negative melanoma cell line repress p53 expression.…”
Section: Discussionsupporting
confidence: 93%
“…These deep DCT+ cells also have HIF‐1 α and Bcl‐2 positive staining, both patterns that assist with resistance to hypoxia and apoptosis. However, reports of DCT expression differ; DCT has been found in 67% nevi, 83% primary and 100% metastatic melanomas by some , but others found DCT decreased from primary melanomas (44%) to metastases (24%) , or that similar levels were present in 85% of primary and 78% of metastatic melanomas . It has been reported that the separation of expression of TYR and DCT proteins in melanoma is an early molecular event in transformation, and the acquisition of Bcl‐2 and HIF‐1 α expression in the dermis is later event leading to metastases, with HIF‐1 α leading to downregulation of MITF and its targets, causing dedifferentiation and increased invasion .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation